Equations for second moments of solutions of a system of linear differential equations with random semi-Markov coefficients and random input - Lapshin, A. L. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We derive equations that determine second moments of a random solution of a system of Itô linear differential equations with coefficients depending on a finite-valued random semi-Markov process. We obtain necessary and sufficient conditions for the asymptotic stability of solutions in the mean square with the use of moment equations and Lyapunov stochastic functions.